B Cells as a Therapeutic Target in Paediatric Rheumatic Disease - Wilkinson, Meredyth G. Ll; Rosser, Elizabeth C. (Frontiers in Immunology, 2019)
B cells carry out a central role in the pathogenesis of autoimmune disease. In addition to the production of auto-antibodies, B cells can contribute to disease development by presenting auto-antigens to autoreactive T cells and by secreting pro-inflammatory cytokines and chemokines which leads to the amplification of the inflammatory response. Targeting both the antibody-dependent and antibody-independent function of B cells in adult rheumatic disease has led to the advent of B cell targeted therapies in clinical practice. To date, whether B cell depletion could also be utilised for the treatment of paediatric disease is relatively under explored. In this review, we will discuss the role of B cells in the pathogenesis of the paediatric rheumatic diseases Juvenile Idiopathic Arthritis (JIA), Juvenile Systemic Lupus Erythematosus (JSLE) and Juvenile Dermatomyositis (JDM). We will also explore the rationale behind the use of B cell-targeted therapies in paediatric rheumatic disease by highlighting new case studies that points to their efficacy in JIA, JSLE and JDM.